A new vision for internal audit. Issue 1 (5th January 2015) - Chambers, Andrew D.; Odar, Marjan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore how internal auditing may recover from being one of the corporate governance gatekeepers that failed to prevent the global financial crisis. Design/methodology/approach – This paper draws on the theory of professions and provides a brief analysis of internal auditing history, ending with an appraisal of contemporary status. Findings – Internal auditing has not been "fit for purpose" and can be enhanced. Low expectations of internal audit are currently addressed by enhanced guidelines from a number of parties. Internal audit needs to move firmly into the corporate governance space – to audit corporate governance more effectively and to provide more dependable assurance to boards. Practical implications – The global Institute of Internal Auditors can use recent enhanced internal auditing guidelines as a springboard to regain their lead. Internal audit needs to cut the umbilical cord that ties it to management. The accepted "dual reporting" of internal audit is flawed. Social implications – Society cedes professional status to an occupational group when it is in society's best interests to do so. An attribute of a profession is its accent on serving the public interest. It is unsatisfactory that, five years after the global financial crisis broke, the international Standards for internal auditing still do not articulate the correct professional conduct on making external disclosures in the public interest when internal auditors are aware of serious wrongdoing not satisfactorily addressed internally. Originality/value – This paper comprises a conceptual analysis to challenge the internal audit profession.